Seasonal Variation in the Fatty Acid Composition and Antioxidant Content of Three Air Breathing Fishes of Loktak Lake of Manipur, India - D, Angom Amala; Sarojnalini, Chungkham (Asian Journal of Biological and Life Sciences)
The present study deals with the determination of Fatty acid composition and antioxidant content of three air breathing fishes Anabas testudineus, Clarias batrachus and Channa punctata of Loktak lake of Manipur, India for different seasons. The FAME was prepared from the extracted lipid using boron-triflouride and DPPH radical scavenging method was used to measure antoxidant activity. Fatty acids like SFA, MUFA and PUFA were detected in all the three fishes. SFAs were dominant in all the three fishes. SFAs like stearic acid was dominant in Anabas testudineus and Clarias batrachus whereas myristic acid was dominant in Channa punctata in all the seasons. MUFA like Oleic acid was dominant in Anabas testudineus and Channa punctata in all the seasons. PUFA like arachidonic acid was dominant in Clarias batrachus and Channa punctata in all the seasons. Antioxidant was detected in all the three fishes and was recorded higher in winter season in all the three fishes. The quantity of FAs and antioxidant varied in all the three fishes in all the seasons. The results of the present findings could be helpful to the nutritionists, dieticians, researchers, fish farmer, etc for future references.
Keywords: Air breathing fishes; Antioxidant; Fatty acids; Seasonal variation